PERAN GURU DALAM MENGATASI PELANGGARAN TATA TERTIB SISWA KELAS V SDN 82 SINGKAWANG - Deva Aprilia; Wasis Suprapto; Dewi Mariana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted with the discovery of problems at SDN 82 Singkawang, namely there are still students who violate the rules. This research aims to: 1) Knowing the types of violations of the rules of the VA class students at SDN 82 Singkawang; 2) Describe the factors that cause violations of the VA class discipline at SDN 82 Singkawang; 3) Describe the role of teachers in overcoming violations of the VA class discipline at SDN 82 Singkawang. This research design is qualitative research with a type of case study research. The informants in this study were the fifth grade teacher, 5 fifth grade students, and the principal of SDN 82 Singkawang in the 2023/2024 school year. This research was obtained through observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and data conclusion.. The results showed 1) The types of rule violations that occurred were students not doing homework, being late, not wearing complete uniforms, and speaking harshly. 2) Factors that cause violation of the rules are lack of desire to comply with the rules, friends and teachers. 3) The role of the teacher as a mentor has been carried out well but the teacher is still lacking in inviting students to discipline in worship. The role of the teacher as a teacher educator is still less assertive in giving punishment. The role of the teacher as a motivator is still lacking in providing rewards. ABSTRAK Penelitian ini dilakukan dengan ditemukannya permasalahan di SDN 82 Singkawang yaitu masih terdapat siswa yang melanggar tata tertib. Penelitian ini bertujuan : 1) Mengetahui jenis pelanggaran tata tertib siswa kelas VA di SDN 82 Singkawang; 2) Mendeskripsikan faktor-faktor yang menyebabkan pelanggaran tata tertib siswa kelas VA di SDN 82 Singkawang; 3) Mendeskripsikan peran guru dalam mengatasi pelanggaran tata tertib siswa kelas VA di SDN 82 Singkawang. Desain penelitian ini yaitu penelitian kualitatif dengan jenis penelitian studi kasus. Subjek dalam penelitian ini adalah wali kelas V, 5 orang siswa kelas V, dan kepala sekolah SDN 82 Singkawang tahun ajaran 2023/2024. Penelitian ini didapat melalui observasi, wawancara dan dokumentasi. Teknik analisis data yang digunakan adalah reduksi data, penyajian data dan menyimpulkan data. Hasil penelitian menunjukkan 1) Jenis pelanggaran tata tertib yang terjadi adalah siswa tidak mengerjakan PR, terlambat, tidak menggunakan seragam lengkap, serta berbicara kasar. 2) Faktor-faktor yang menyebabkan pelanggaran tata tertib yaitu kurangnya keinginan untuk mematuhi tata tertib, teman dan guru. 3) Peran guru sebagai pembimbing sudah dilaksanakan dengan baik namun guru masih kurang dalam mengajak peserta didik disiplin dalam beribadah. Peran guru sebagai pendidik guru masih kurang tegas dalam memberikan hukuman. Peran guru sebagai motivator masih kurang dalam memberikan reward.